Morphology and Taxonomy of Isopoda Anthuroidea (Crustacea) from Sulawesi with description of six new species - Annisaqois, Manikmayang; Wägele, J. Wolfgang (European Journal of Taxonomy, 2021)
This is a first inventory of Isopoda Anthuroidea from near-shore marine sites in Sulawesi. The material was collected from reefs, sea-grass beds and mangroves of the Minahasa Peninsula in North Sulawesi. Specimens were washed out from benthos samples collected in shallow water. The new species Hyssura reptans sp. nov., Kupellonura indonesica sp. nov., Kupellonura macaroni sp. nov., Pendanthura bangkaensis sp. nov., Expanathura marcoi sp. nov., and Colanthura gerungi sp. nov. are described. We discovered that in Colanthura the mandible is fused to the cephalothorax, a unique feature among isopods. Expanathura collaris (Kensley, 1979) is described from Bangka Island and several differences between other Indo-Pacific populations are discussed.